3-Year-Olds' Perseveration on the DCCS Explained: A Meta-Analysis. Issue 4 (8th August 2017) - Landry, Oriane; Al-Taie, Shems; Franklin, Ari
ABSTRACT: The Dimensional Change Card Sort (DCCS) task is a widely used measure of preschoolers' executive function. We combined data for 3, 290 3-year-olds from 37 unique studies reporting 130 experimental conditions. Using raw pass/fail counts, we computed the pass rates and chi-squared value for each against chance (50/50) performance. We grouped data according to DCCS variants and computed the standard pass rate and chi-squared and phi for each variant relative to standard. For all standard versions, the mean pass rate was 36%. We compared all other variants to the standard and found robust improvements in performance for manipulations that involved spatial separation of the conflicting dimensions, use of distraction between pre and post-switch, elimination of all conflict, and extra practice. We also found that negative priming offers a better explanation for 3-year-olds' perseveration than attentional inertia . The results support a theoretical model of 3-year-olds' performance based on inhibitory control.